#### Answer

$-3x^{3}$

#### Work Step by Step

$\sqrt[3] (-27x^{9})=-3x^{3}$, because $(-3x^{3})^{3}=-3x^{3}\times -3x^{3}\times -3x^{3}=(-3\times-3\times-3)\times x^{3+3+3}=-27x^{9}$

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

$-3x^{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.